2020
DOI: 10.1038/s41598-020-71413-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative quantitative LC–MS/MS analysis of 13 amylase/trypsin inhibitors in ancient and modern Triticum species

Abstract: Amylase/trypsin inhibitors (ATIs) are major wheat allergens and they are also implicated in causing non-celiac gluten sensitivity and worsening other inflammatory conditions. With only few studies on ATI contents in different Triticum species available so far, we developed a targeted liquid chromatography-tandem mass spectrometry (LC–MS/MS) method based on stable isotope dilution assays to quantitate the 13 most important ATIs in a well-defined sample set of eight cultivars of common whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 42 publications
11
56
1
1
Order By: Relevance
“…Consistent with the low ATI concentrations determined by MS (44,60), einkorn showed no inhibition of Coleopteran insect or mammalian α-amylases (70-74) and the lowest TRL4activating potential compared to other wheat species (50). However, einkorn inhibited α-amylase from Lepidopteran insects (72) and contains a trypsin inhibitor similar to rye and barley (70) which may explain the high trypsin inhibitory activity (44).…”
Section: Atis In Other Types Of Wheat and Related Cerealsmentioning
confidence: 55%
See 2 more Smart Citations
“…Consistent with the low ATI concentrations determined by MS (44,60), einkorn showed no inhibition of Coleopteran insect or mammalian α-amylases (70-74) and the lowest TRL4activating potential compared to other wheat species (50). However, einkorn inhibited α-amylase from Lepidopteran insects (72) and contains a trypsin inhibitor similar to rye and barley (70) which may explain the high trypsin inhibitory activity (44).…”
Section: Atis In Other Types Of Wheat and Related Cerealsmentioning
confidence: 55%
“…hexaploid wheat whereas the proportion of tetrameric CM-type inhibitors is higher in tetraploid wheats (60).…”
Section: Atis In Other Types Of Wheat and Related Cerealsmentioning
confidence: 91%
See 1 more Smart Citation
“…This indicates the presence of proteins with M r around about 14 kDa or lower. This may result from, e.g., α-amylase/trypsin-inhibitors that have a M r of about 12-16 kDa, but further analyses are required to unambiguously identify these proteins [41].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, some wheat proteins can cause adverse inflammatory reactions in humans: (1) certain gluten peptide sequences trigger small intestinal and extraintestinal T cell activation and inflammation in patients with celiac disease [10,11]; (2) the family of wheat alpha-amylase/trypsin inhibitors (ATIs) stimulate intestinal innate immune cells via the activation of Toll-like receptor 4 and promote intestinal and extraintestinal inflammation [12][13][14][15][16][17]; (3) numerous wheat albumins and globulins, such as serpins, lipid transfer proteins, β-amylases and ATIs, as well as a few gluten proteins, can elicit respiratory and nutritional immediate allergic reactions [18][19][20][21]; and (4) a novel form of nutritional wheat allergy with an immediate intestinal, but a delayed clinical, reaction to wheat proteins is highly prevalent among patients with "irritable bowel syndrome" [22,23]. The first studies showed that wheat cultivars largely differ in the compositions of ATIs [24,25] or of the 33-mer α-gliadin peptide, a key immunogen for T cells in patients with celiac disease [26]. However, investigations of a large number of proteins across many wheat cultivars grown under different environmental conditions are lacking.…”
Section: Introductionmentioning
confidence: 99%